Osteointegration of PLLA/β-TCP Biocomposite Anchors Used in Coracoid Transfer Procedures for Shoulder Instability: Quantitative Computed Tomography With a Minimum 2-Year Follow-up. Issue 12 (13th December 2022) - Shen, Guangsi; Ma, Yinguang; Zhang, Shuhan; Song, Qingfa; Tang, Chengyang; Zhang, Yaxuan; Liu, Guihu; Liu, Qiang; Shao, Zhenxing; Cui, Guoqing
Background: Biocomposite anchors have been a popular choice for use in coracoid transfer procedures for shoulder instability and are hypothesized to allow bone ingrowth. Purpose: To quantitatively evaluate the osteointegration of 85% PLLA/15% β-TCP biocomposite anchors used in the coracoid transfer procedure for shoulder instability. Study Design: Case series; Level of evidence, 4. Methods: We performed a retrospective case series of abstracted data from the records of 74 patients who underwent coracoid transfer procedures with biocomposite anchors. Computed tomography was performed at 24 months postoperatively. A total of 4 researchers independently reviewed the computed tomography images. The density (in Hounsfield unit [HU] values) of the anchor tunnels, glenoid, and subscapularis was assessed, and osteointegration of the anchor tunnels was evaluated with HU values, the quantitative ossification quality score (QOQS), and tunnel widening. Results: Included were 74 patients (58 male, 16 female), involving 76 shoulders and 124 biocomposite anchors. At ≥24-month follow-up, 72 of 124 (58.06%) anchor tunnels were classified as QOQS type 1, including 12 completely ossified tunnels and 60 almost completely ossified tunnels. Some degree of ossification (QOQS types 1-3) was observed in 118 (95.16%) anchor tunnels. Overall, 3 anchor tunnels were enlarged (QOQS type 5). The mean HU value of the anchor tunnels was 339.75, which was significantly higher than the preoperative HU value of the glenoid vault (262.19). Among the 124 anchor tunnels, 79 had HU values higher than their glenoid HU values, and 45 had lower HU values than their glenoid HU values. In the comparison of tunnel HU values at 12 versus ≥24 months, the HU value at ≥24 months was significantly higher. A total of 20 anchor tunnels widened. Conclusion: Among 124 anchor tunnels, 95.16% showed ossification, 58.06% were completely or nearly completely ossified, and 3 were enlarged. The HU value of the anchor tunnel increased over time.